2020
DOI: 10.1101/2020.07.15.205492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical overstimulation causes acute injury and synapse loss followed by fast recovery in lateral-line neuromasts of larval zebrafish

Abstract: Noise exposure damages sensory hair cells, resulting in loss of synaptic connections with auditory nerves and hair-cell death. The cellular mechanisms underlying noise-induced hair-cell damage and subsequent repair are not completely understood. Hair cells in neuromasts (NMs) of larval zebrafish are structurally and functionally comparable to mammalian hair cells but undergo robust regeneration following damage. We therefore developed a model for noise-induced hair-cell damage in this highly tractable system. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 84 publications
(116 reference statements)
2
22
0
Order By: Relevance
“…It has recently been shown that Vglut3 -/null mutant mice do not lose hair-cell synapses following noise exposure, supporting a role for synaptic transmission in noise-induced synapse loss (Kim et al, 2019). Additionally, in our previous study of mechanical injury in the zebrafish lateral line, we observed significantly more severe mechanically-induced hair-cell synapse loss in fish when glutamate clearance from the synapse was pharmacologically blocked, suggesting synapse loss can be exacerbated by excess glutamate in the synaptic cleft (Holmgren et al, 2021). Our results here show that mpv17 a9/a9 hair cells have reduced FM1-43 uptake indicating reduced hair-cell transduction (Fig.…”
Section: Mechanical Overstimulation and Hair-cell Synapse Losssupporting
confidence: 62%
See 3 more Smart Citations
“…It has recently been shown that Vglut3 -/null mutant mice do not lose hair-cell synapses following noise exposure, supporting a role for synaptic transmission in noise-induced synapse loss (Kim et al, 2019). Additionally, in our previous study of mechanical injury in the zebrafish lateral line, we observed significantly more severe mechanically-induced hair-cell synapse loss in fish when glutamate clearance from the synapse was pharmacologically blocked, suggesting synapse loss can be exacerbated by excess glutamate in the synaptic cleft (Holmgren et al, 2021). Our results here show that mpv17 a9/a9 hair cells have reduced FM1-43 uptake indicating reduced hair-cell transduction (Fig.…”
Section: Mechanical Overstimulation and Hair-cell Synapse Losssupporting
confidence: 62%
“…Thus, loss of Mpv17 increases sensitivity to neomycin-induced hair-cell death. We have previously reported a protocol to mechanically overstimulate zebrafish lateral line organs using strong water current (Holmgren et al, 2021). This stimulation resulted in phenotypes including mechanical disruption of neuromast morphology, loss of hair cells, neurite retraction, and loss of hair-cell synapses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hair cells of the inner ear can be damaged or lost after noise exposure, ototoxicity, or as part of normal aging. Like their counterparts in the ear, lateral line hair cells can also be damaged by exposure to ototoxic drugs or by mechanical trauma (Harris et al, 2003 ; Hernández et al, 2006 ; Uribe et al, 2018 ; Holmgren et al, 2020 ). Many of the signaling pathways that mediate hair cell death have been identified (e.g., Wagner and Shin, 2019 ).…”
Section: Introductionmentioning
confidence: 99%